DFT aspects of the elastic, mechanical, magnetic, thermodynamic and optical properties of Ce3XY perovskites. Issue 3 (1st February 2022) - Güler, E.; Güler, M.; Uğur, Ş.; Uğur, G.
ABSTRACT: We report some unclarified physical properties of Ce3 XY (X = Al, In and Y = C, N) inverse cubic perovskites by conducting a density functional theory (DFT) study. The elastic, mechanical, magnetic, thermodynamic and optical properties of these compounds were addressed. Obtained elastic data prove the mechanical stability, elastic anisotropy and brittle mechanical character for all investigated compounds. Vickers hardness values follow the Ce3 InC > Ce3 AlN > Ce3 InN > Ce3 AlC sequence. All compounds show ionic bonding except the Ce3 AlC in which covalent bonding is dominant. Besides, all compounds exhibit ferromagnetic ordering. The calculated total magnetic moments arise between 2.22μB and 2.67μB . Their magnitudes follow Ce3 InN > Ce3 AlN > Ce3 InC > Ce3 AlC range. Temperature dependence of heat capacity, entropy, thermal conductivity and Debye temperature of the compounds exhibit identical characteristics of typical solids. Optical property results suggest that these compounds are both good optical absorbers and conductors, in particular for practical applications in the ultraviolet (UV) region.